Unraveling the luminescence secrets of turquoise nucleus cultivated pearls - Yan Li; Qing Su; Wei Shao; Lei Li (Scientific Reports)
Abstract Turquoise nucleus cultivated (TNC) pearls represent a distinctive variety which are distinguished by their unique nucleus and remarkable aesthetic appeal. In contradistinction to the common pearls, which were formed by a shell nucleus, TNC pearls are characterized by a nucleus composed of a turquoise-like mineral. This study presents a comprehensive analysis of the spectral characteristics of TNC pearls. It reveals that TNC pearls grew in seawater, as indicated by the peak area ratio of Sr to Ca in X-ray fluorescence data. Additionally, the relatively subdued luster of TNC pearls is hypothesized to result from the specific nature of their nucleus material. It is noteworthy that the nuclei of these pearls are not composed of natural turquoise because their infrared spectrum exhibits characteristic absorption peaks of gibbsite at 1025 cm-1 and 669 cm-1, alongside peaks indicative of organic compounds. It is proposed that the nucleus consists of a gibbsite, encased within a protective layer of organic compounds during the carving process. In addition, three-dimensional (3D) fluorescence and photoluminescence spectroscopy demonstrate that the fluorescence characteristics of TNC pearls are comparable to those of traditional cultivated pearls. This study analyzes the samples derived from black-lipped oysters and golden-lipped oysters respectively. This finding underscores the efficacy of 3D fluorescence and photoluminescence spectroscopy as reliable methods for identifying these new pearl species.